ANALYSIS OF MODIFYING RISK FACTORS FOR THE DEVELOPMENT OF RECURRENT COURSE IN OBSTRUCTIVE BRONCHITIS IN CHILDREN - Xusainova , Shirin Kamildjonovna; Makhmujanova , Sitorabonu Rustamovna (Educational Research in Universal Sciences, 2024)
Respiratory diseases occupy a special place in the structure of general morbidity among children. In cases of repeated (2-3 times or more during the year) episodes of bronchitis with broncho-obstructive syndrome, recurrent obstructive bronchitis is formed. Recurrent obstructive bronchitis in children is one of the most pressing problems in pulmonology. We examined 80 children with broncho-obstructive syndrome, who were divided into II groups: Group I (main) consisted of 40 children with recurrent obstructive bronchitis, and Group II (control) - 40 children with newly diagnosed obstructive bronchitis. The results of the statistical analysis showed that the risk of developing relapses of obstructive bronchitis in group I of sick children (IP1) did not differ much in comparison with group II of patients (IP0) in the following factors: pathology of pregnancy (0.82 and 0.42), pathology in childbirth (0.72 and 0.48), chronic foci of infection in the mother (0.42 and 0.33), exacerbation of chronic diseases in the mother (0.53 and 0.33), gestosis in pregnant women (0.33 and 0.33), borderline maternal age (0.48 and 0.33), prematurity (0.11 and 0.08) these pathologies were found almost equally in the main and control groups. At the same time, the leading reliable modifying factors are hereditary burden of bronchopulmonary pathology, allergic diseases of the mother, bronchial asthma in the family, early mixed and artificial feeding, rickets, malnutrition, HIE, atopic dermatitis, “frequently ill children.”